2004
DOI: 10.1111/j.1365-2966.2004.08273.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation of ices near massive stars: models based on laboratory temperature programmed desorption data

Abstract: Hot cores and their precursors contain an integrated record of the physics of the collapse process in the chemistry of the ices deposited during that collapse. In this paper, we present results from a new model of the chemistry near high‐mass stars in which the desorption of each species in the ice mixture is described as indicated by new experimental results obtained under conditions similar to those in hot cores. Our models show that provided there is a monotonic increase in the temperature of the gas and du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
393
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 282 publications
(404 citation statements)
references
References 12 publications
9
393
0
2
Order By: Relevance
“…At ≈ 10 4.5 years the sudden jump in abundance of methyl formate and ethyl cyanide is due to the evaporation of these species from the grain mantle surface. At late times varying the final mass of the star does not seem to affect the fractional abundances of the complex species we consider; however, as expected (see Viti et al 2004), a higher mass implies an earlier icy mantle evaporation. In general a very low abundance of COMs implies a young age with the exception of methyl cyanide (but see Sect.…”
Section: Chemical Modellingmentioning
confidence: 80%
See 3 more Smart Citations
“…At ≈ 10 4.5 years the sudden jump in abundance of methyl formate and ethyl cyanide is due to the evaporation of these species from the grain mantle surface. At late times varying the final mass of the star does not seem to affect the fractional abundances of the complex species we consider; however, as expected (see Viti et al 2004), a higher mass implies an earlier icy mantle evaporation. In general a very low abundance of COMs implies a young age with the exception of methyl cyanide (but see Sect.…”
Section: Chemical Modellingmentioning
confidence: 80%
“…Results of chemical models in the past have suggested that determining abundance ratios of typical hot core tracers (e.g. CH3CN) as well as sulphur-bearing species could serve as indicators of both mass and age (Hatchell et al 1998;Viti et al 2001;Buckle & Fuller 2003;Viti et al 2004). However much care has to be taken due to the fact that most species do not necessarily trace the very inner part of the core and their emission region probably spans a range of densities and temperatures that make the interpretation difficult (Wakelam et al 2004).…”
Section: Spectral Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…The present model, UCL DCHEM, is an adaptation of the UCL CHEM model (Viti & Williams 1999;Viti et al 2004), which in its original form did not include a deuterium network. 2 This paper is organized as follows: in §2 we describe our model; in §3 we present the results of the grid of models we ran.…”
Section: Introductionmentioning
confidence: 99%